Hazard Level and Risk of Mount Marapi Cold Lava Flood Disaster Based on Geographic Information System (Gis) in Tanah Datar Regency, West Sumatra, Indonesia - binti Muhammad Yusoff, Safiah Yusmah; Rahadhatul Aisy; Rosmadi bin Fauzi; Aprizon Putra (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
Cold lava floods are a significant threat in the area around Mount Marapi, West Sumatra, Indonesia. Flows of volcanic material carried by rain after an eruption can cause major damage to settlements, farmland, and infrastructure. Geographic Information System (GIS) technology is a very effective tool to identify the level of danger and risk of this disaster. This article examines a GIS-based approach in the assessment of the hazards and risks of cold lava floods in Tanah Datar Regency. The mapping shows a flood path in the watershed from the slopes of Mount Marapi, with a high-risk area of 27,480 hectares within 300 meters of the riverbank. Risk analysis shows that low-risk areas include 6,889.28 hectares, medium-risk 8,496.71 hectares, and high-risk 3,999.63 hectares, spread across several sub-districts.